EDUKASI KESEHATAN TENTANG BAHAYA PERGAULAN BEBAS PADA REMAJA DI KELURAHAN CAWANG JAKARTA TIMUR - Sri Melfa Damanik (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
Adolescence is a period of transition from childhood to adulthood, and an unstable period in which adolescents seek identity. The problem that occurs in adolescence is that teenagers do not know the dangers of promiscuity which consists of smoking, using drugs and free sex. The purpose of implementing this Community Service (PkM) is to increase the knowledge of teenagers about the dangers of promiscuity. A total of 139 students and students and teachers participated in PkM activities. The method of implementing PkM is conducting online health education zoom meetings by giving pretest and post-test questionnaires filled out by 94 students and 6 teachers. The results of PkM show that there is an increase in good knowledge from 6 respondents (6%) to 8 respondents (8%). Knowledge is sufficient from 20 respondents (20%) to 74 respondents (74%). Knowledge is less than 74 respondents (74%) to only 8 (18%) respondents. Providing education regularly in the community can be one of the right solution to improve public helath status and reduce promiscuity among adolescents in Indonesia. Keywords: Dangers of Promiscuity; Teenager; Smoke; Drugs; Free sex